Design of composite members with curvilinear fiber trajectories. (December 2019) - Polilov, Alexander N; Tatus, Nikolay A; Tian, Xiaoyong; Hao, Liu
Abstract: The design possibility of shaped constant area composite tensile test specimen and leaf spring is shown and the last can provide by chosen geometry threefold mass reduction for the given level of stored elastic energy. The use of unidirectional GFRP (glass fiber reinforced plastic) makes it possible to reduce the mass by approximately 15 times in compare with the steel analog for the same strength and stored energy requirements. The curvilinear trajectories of fibers tracing around the hole or rivet/bolt connection make it possible to increase load carry capacity many times.